A Parental Request for an Unproven Treatment for a Rare Pediatric Cancer: Sound Reasons for Not Going Off-Label - Hedlin, Margot (The Hastings Center report, 2026)
We present the case of a three-year-old in remission from ependymoma whose parents requested off-label metformin in the hope that it could reduce her chance of recurrence. A prominent specialist who was developing a clinical trial studying metformin as an adjunctive treatment for children with relapsed ependymoma had recommended metformin for the patient based on theoretical chance of benefit. The child's primary neuro-oncologist sought an ethics consult, as he did not believe that prescribing metformin off-label to this patient was ethical. We argue that he should not prescribe the medication. Current data do not support its use, and it carries nontrivial risks. Moreover, prescribing unproven treatments outside of a trial risks giving families false hope, undermining clinical research, and creating pressure on physicians to offer unproven interventions. Social media amplifies these requests, shaping parental decision-making and potentially spreading unvalidated practices. Physicians may respond compassionately while declining to provide interventions outside standard care. This case highlights the ethical boundaries of off-label prescribing in pediatric oncology.